2020
DOI: 10.1128/msphere.00334-20
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Viral Partitioning in a Marine-Derived High Arctic Lake

Abstract: High-latitude, perennially stratified (meromictic) lakes are likely to be especially vulnerable to climate warming because of the importance of ice in maintaining their water column structure and associated distribution of microbial communities. This study aimed to characterize viral abundance, diversity, and distribution in a meromictic lake of marine origin on the far northern coast of Ellesmere Island, in the Canadian High Arctic. We collected triplicate samples for double-stranded DNA (dsDNA) viromics from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 78 publications
2
19
1
Order By: Relevance
“…These methods have greatly advanced viral ecology from the identification of novel viruses to the global distribution of viruses. Studies from a variety of environments such as thawing permafrost [13], mangroves [14], arctic lakes [15], freshwater lakes [16], deep sea sediments [17], the terrestrial subsurface [18,19], and especially seawater [20][21][22] have suggested that prokaryotic viruses act as key agents in natural ecosystems via a range of interactions with their microbial hosts. Viruses can influence organic carbon and nutrient turnover by top-down control of microbial abundance via lysis of cells and subsequent release of cellular contents during lytic infection [23].…”
Section: Introductionmentioning
confidence: 99%
“…These methods have greatly advanced viral ecology from the identification of novel viruses to the global distribution of viruses. Studies from a variety of environments such as thawing permafrost [13], mangroves [14], arctic lakes [15], freshwater lakes [16], deep sea sediments [17], the terrestrial subsurface [18,19], and especially seawater [20][21][22] have suggested that prokaryotic viruses act as key agents in natural ecosystems via a range of interactions with their microbial hosts. Viruses can influence organic carbon and nutrient turnover by top-down control of microbial abundance via lysis of cells and subsequent release of cellular contents during lytic infection [23].…”
Section: Introductionmentioning
confidence: 99%
“…These methods have greatly advanced viral ecology from the identification of novel viruses to the global distribution of viruses. Studies from a variety of environments such as thawing permafrost 12 , mangroves , arctic lakes 14 , freshwater lakes , and particularly seawater [16][17][18] have suggested that prokaryotic viruses act as key agents in natural ecosystems via a range of interactions with their microbial hosts. Viruses can influence organic carbon and nutrient turnover by top-down control of microbial abundance via lysis of cells and the subsequent release of cellular contents during lytic infection 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Environments such as the soil (Williamson et al, 2017), deep sea (Danovaro et al, 2008), and glaciers (Bellas et al, 2015) harbor many largely unknown pathogenic viruses and microorganisms. Meanwhile, global warming may facilitate the release of ancient pathogenic microorganisms and advance the population dynamics of viruses (Frenken et al, 2020;Labbé et al, 2020;Zhong et al, 2020), which can infect humans health through extreme weather or through the carriage of plants and animals. The soil pathogenic microbes, indigenous or exogenous pathogenic microbes in the soil that have the potential to cause disease to humans, are typically in balance with other microbes due to subtle interactions and soil properties, such as Salmonella, of which longevity in the soil depends on the interaction with indigenous microorganisms (Locatelli et al, 2013;Schierstaedt et al, 2020).…”
mentioning
confidence: 99%